Hunting in Mallorca from a geographical point of view - Antoni Barceló Adrover; Miquel Grimalt Gelabert; Jaume Binimelis Sebastián (Investigaciones Geográficas)
According to the official data about the holders of hunting licenses and hunting areas provided by the hunting service of the Local Development Department - Consell de Mallorca, a detailed study is carried out on the social and territorial implications of the hunting activity on the island. Firstly, the spatial distribution, age, gender, type of license and origin of the hunters are analysed and, secondly, the category, location and extension of the hunting and non-hunting areas are examined. Administrative boundaries are used as a reference and depending on the hunting land area index per person, a categorization is established in municipalities that are requesting, bidding for or are balanced in terms of hunting spaces. Finally, the hunting situation is evaluated, which is currently conditioned by changes in land use and social questioning about the activity. In this sense, hunting planning is fundamental.